Shape control of laminated panels using piezoelectric actuators - Moita, José Mateus Simões (2009)
This paper presents a finite element formulation based on the classical laminated plate theory for laminated structures with integrated piezoelectric layers or patches, acting as actuators.The finite element model is a single layer trinaguular nonconforming plate/shell element with 18 degrees of fredom for the generalized displacements, and one electrical potential degree of freedom for each piezoelectric element elemenet layer or patch. An optimization of the patches position is perfomed to maximize the piezoelectric actuators efficiency as well as,the electric potential distribution is serach to reach the specified strusctura transverse displacement distribution is search to reach the specified structures trsnsverse displacement distribution (shape control). A gradient based algorithm is used for this purpose.Results are presented and discussed.